2016
DOI: 10.4103/2230-8229.189134
|View full text |Cite
|
Sign up to set email alerts
|

Parents′ perception of children′s obesity, in Al-Qassim, Saudi Arabia

Abstract: Background and Objectives:Although the prevalence of childhood obesity has increased significantly in Saudi Arabia, parents are unable to appreciate obesity in their child. The objective of the study was to identify the percentage of parents who misclassify the status of child's weight, and determine whether there is a difference between those parents whose children are overweight and obese and those with children of normal weight.Materials and Methods:This cross-sectional study included 601 children aged 6-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…Similarly, this systematic review aimed at identifying the differences between parental perception and the actual weight status of children worldwide, this finding reveals that majority of studies used verbal descriptions 51 . This review shows that parents' wrong perception regarding their children weight status was higher in parents compared to only mother (90%, 30% respectively) 23,24 , this finding is in accordance with previous findings of other study who reported a higher wrong perception in parents compared to only mother 52 , this can be explained by mothers having more concerned than fathers about their child's weight status. Noticeably, this systematic review revealed that obese children are often perceived as normal-weight children and not vice versa.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, this systematic review aimed at identifying the differences between parental perception and the actual weight status of children worldwide, this finding reveals that majority of studies used verbal descriptions 51 . This review shows that parents' wrong perception regarding their children weight status was higher in parents compared to only mother (90%, 30% respectively) 23,24 , this finding is in accordance with previous findings of other study who reported a higher wrong perception in parents compared to only mother 52 , this can be explained by mothers having more concerned than fathers about their child's weight status. Noticeably, this systematic review revealed that obese children are often perceived as normal-weight children and not vice versa.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of studies demonstrate parental underestimation of child weight status [ 12 , 16 , 32 ]. Considerable research has been devoted to parental perceptions of children’s weight during late childhood or adolescent stages [ 1 , 2 , 36 ] and also during the toddler years [ 5 , 14 , 19 , 26 ]. Although the literature suggests that parental awareness of weight problems may be particularly low for younger children [ 15 , 29 , 35 ], there has been relatively less attention paid to examining parental weight perception during the younger years particularly for preschool children [ 7 , 16 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parents attitude is of paramount importance in obesity. Underestimation of body weight among children's parents was reported locally [16] and internationally [17]. Children's parents in Qassim misclassified most of overweight and more than half of obese children [16].…”
Section: Discussionmentioning
confidence: 99%